Evaluation of a microarray for genotyping polymorphisms related to xenobiotic metabolism and DNA repair. (October 2003) - Landi, Stefano; Gemignani, Federica; Gioia-Patricola, Lydie; Chabrier, Amélie; Canzian, Federico
We present an oligonucleotide microarray ("MetaboChip") based on the arrayed primer extension (APEX) technique, allowing genotyping of single nucleotide polymorphisms (SNPs) in genes of interest for cancer susceptibility and pharmacogenetics. APEX consists of a sequencing reaction primed by an oligonucleotide anchored with its 5′ end to a glass slide and terminating one nucleotide before the polymorphic site. The extension with one fluorescently labeled dideoxynucleotide complementary to the template reveals the polymorphism. Ninety-three SNPs in 42 genes were selected among those resequenced in the context of the SNP500 project, using a set of 102 reference DNA samples from the Coriell Biorepository. Selected SNPs belong to the following genes: ADH1B, ALDH2, APEX, CDKN2A, COMT, CYP1A1, CYP1A2, CYP1B1, CYP2A6, CYP2C19, CYP2C9, CYP2E1, CYP3A4, DRD2, DRD4, EPHX1, ERCC1, ERCC2, ERCC4, ERCC5, GRPR, GSTA4, GSTM3, GSTP1, GSTT2, LIG3, MDM2, MGMT, MPO, NAT1, NAT2, NQO1, OGG1, PCNA, POLB, SLC6A3, SOD2, TP53, XRCC1, XRCC2, XRCC3, and XRCC9 . We assessed the performance of APEX by comparing the results obtained with MetaboChip against those reported by the SNP500. Among 88 SNPs that yielded signals, 6 showed less than 99% of concordance, whereas 82 performed accurately, showing that APEX is a reliable and sensitive genotyping method.